Characteristics and hemolysis analysis of centrifugal blood pumps under different speed modulations - Su, Chengxuan; Jin, Donghai; Liu, Guangmao; Li, Shulei; Gui, Xingmin (Frontiers in Physiology, 2025)
IntroductionConstant-speed methods are widely applied and studied in rotary blood pumps. However, various speed modulation which have been used in commercial blood pump lacks validation of the ventricular assist capability and hemolysis potential.MethodsThis study investigates the hydrodynamic performance and hemolysis of a rotary ventricular assist device under sinusoidal speed modulation, focusing on the combined effects of phase, baseline speed, and speed fluctuation amplitude.ResultsComputational fluid dynamics (CFD) coupled with a dynamic cardiovascular model revealed that counter-phase modulation reduces hemolysis index (HI) fluctuations compared to in-phase conditions, while higher baseline speeds increase time-averaged HI due to prolonged exposure to non-physiological shear stress. Larger amplitudes expand the operational range but exacerbate HI variability.DiscussionThese findings demonstrate that phase synchronization critically balances pulsatility and hemocompatibility, providing actionable insights for adaptive speed control strategies in clinical practice.